Ulun Danu Beratan Temple as an Economic Contest Arena in a Multicultural Society - Gede Mahardika; Ketut Suda; I Wayan Winaja (International Journal of Interreligious and Intercultural Studies, 2022)
Ulun Danu Beratan Temple as a Tourist Destination Area (DTA) located in Candikuning Village. The natural beauty of the surrounding causes tourist visits to increase every year. As a DTA, the area outside the Ulun Danu Beratan Temple is used as an arena for economic contestation for a multicultural community. There are several things that make the Ulun Danu Beratan Temple as an arena of economic contestation for a multicultural society such as natural beauty, "identity politics", anthropocentrism modernism, Tri Hita Karana ideology and economics, with an economic contestation process caused by several things such as the development of tourism in Candikuning Village, domestic tourist visits, religious identity, tolerance of the Balinese Hindu community and the entry of non-Hindu communities into Candikuning Village. The contestation has implications for religious life, the sanctity of temples, the social life of the community, such as the value of gotong royong, the ngejot tradition which has begun to fade, as well as the ketog semprong tradition. It also has implications for politics, such as the strengthening of identity politics. In addition, it has implications for the economy such as the creation of employment opportunities and its side effects such as lake pollution. This study uses a multidisciplinary approach to religion and culture and uses interpretive critical qualitative analysis. The theory used analyzes the theory of hegemony, tourism destination development, community change, and sociocultural systems.